ANALISIS NILAI TAMBAH, PENDAPATAN, DAN BAURAN PEMASARAN KOPI PADA AGROINDUSTRI KOPI BUBUK KLANGENAN PRINGSEWU - Abi Zulkarnain, Muhammad; Kasymir, Eka; Saleh, Yuliana (Journal of Food System & Agribusiness, 2023)
This research aims to analyze added value of coffee, income, and marketing mix of coffee in Agroindustry of Coffee Powder Klangenan Pringsewu. This research was conducted in Agroindustry of Klangenan Coffee Powder Pringsewu. This study uses a case study method, with sampling technique are purposive sampling and accidental sampling. Respondents in this research were divide into two, owner of agroindustry and consumer as many as 30 respondents. This study used Hayami’s value added analysis method, R/C total cost, and 7P marketing mix. Data of this research were collected in January 2021 until March 2021. The results show that the added value to the agroindustry was positive, which means that it is feasible to be cultivated and developed, and is included in the labor intensive category. The income of the agroindustry has a revenue ratio (R/C) for the total cost of more than one, which means that the coffee of agroindustry business is profitable and feasible to run. The marketing strategy of agroindustry has implemented the 7P marketing mix component, which the product, place, price, process, people, and physical evidence, where only the promotion component has not been used optimally, and must be developed and considered again.